Characterization of and screening for antagonistic activity of selected microorganisms against fusarium solani on black pepper - Kundat, Franklin Ragai (2014)
Due to environmental concerns of chemical fertilizers and pesticides usage, biological control is emerging as a promising alternative to fulfill the nutrient demand and disease control of black pepper. The general objective of this study was to evaluate the potential of microbes isolated from soil of a rehabilitated forest floor as biological contol agents (BCAs) in inducing root growth and suppressing the development of yellow disease caused by Fusarium solani on early growth of black pepper (var. Kuching). The microbial strains isolated from the soil of rehabilitated forest floor were evaluated for their in vitro antagonistic potential against Fusarium solani. Three microbial isolates, Trichoderma atroviride (UPM23F) showed the best performance followed by Bacillus pumilus (UPM38EB) and Bacillus cereus (UPM41EB) respectively, resulting in a significant inhibition of radial growth of F.solani. The highest colonization (4.77 x 104 ) of black pepper rhizoplane was achieved by T. atroviride. B. pumilus showed the highest colonization (9.01 x 104 ) in internal tissues of root tips. Their symbiotic associations with the host plants enhanced root growth as shown by increment in root length, root biomass, both fresh and dry. The study on microbial inoculants and nitrogen (N) demonstrated the ability of microbial inoculants in improving N uptake and thereby increase N use efficiency of applied chemical fertilizers. Assessment on the plant-microbe interaction showed that the microbial isolates induced production of inducible compounds such as peroxidase (PO), polyphenoloxidase (PPO), and phenylalamine ammonia lyase (PAL). The efficacies of microbial isolates were tested against F. solani. Two timing of inoculations were evaluated: inoculating soils at planting and inoculating soils 14 days before planting. Inoculation with T. atroviride (UPM23F) singly was most effective followed by inoculation with mixture of T. atroviride + B. pumilus (UPM23F+UPM38EB) based on variables such as delay in onset of symptoms, lower percentages (33.33%) in disease severity (DS) and higher percentages (83.80%) in disease reduction (DR). The extent of foliar yellowing was less severe in cuttings inoculated with microbial inoculants as compared to the control. Inoculation of soils prior to planting with microbial inoculants yielded the best results. This study has shown that the microbial isolates tested were effective against F. solani and have plant growth promoting properties and potential to be developed as BCAs. The understanding of biocontrol mechanisms involved in disease suppression would help optimize their biocontrol efficiency. Therefore, further studies in relation to formulation, application frequency and techniques, are essential to maximize the potential of T. atroviride (UPM23F) and B. pumilus (UPM38EB) as BCAs against Fusarium yellow disease of black pepper.